PENGARUH PELATIHAN, KOMPETENSI DAN PENEMPATAN KARYAWAN TERHADAP KINERJA PT. SEMEN BATURAJA (PERSERO) TBK - Ahmad Fadilah; Luis Marnisah; Fakhry Zamzam (Program Magister Manajemen Indo Global Mandiri University, 2020)
The purpose of this study was to determine the results of the analysis of how the effect of training, competence and placement, both partially and simultaneously, on the performance of PT. Semen Baturaja (Persero) Tbk. The sample measurement refers to the Saturated Sample Concept that has been formatted so that it is stated that all populations are samples that are very simple and easy to use, because functionally it only consists of two important columns namely a column for population size (N) and a column for sample size (n). The number of employees of PT. Semen Baturaja (Persero) Tbk as many as 85 people became the population and all were taken as samples. In this study, the type of data used are primary data and secondary data. Data collection techniques using questionnaires, interviews, observation and documentation. Hypothesis testing through t test and F test using SPSS analysis tools. The results of research data output processed with SPPS 23 that training, competence and placement together affect the performance of PT. Semen Baturaja (Persero) Tbk with a significance level of 0.001 <0.05, thus H0 is rejected and H1 can be accepted. That the influence of training, competence and placement together are positive and significant to the performance of PT. Semen Baturaja (Persero) Tbk with an F count of 35, 474> F table4,893. Thus this hypothesis-4 rejects Ho and accepts H1, that together training, competence and placement together positively and significantly influence the performance of PT. Semen Baturaja (Persero) Tbk, with a significance level of 0.026 <0.05 and t arithmetic 2.269> t table 2003 and a 0.306 regression terminated, so that this study was able to confirm between the research theory and the empirical in the field. Conclusion of the study that simultaneous training, competence and placement affect the performance of employees to work more diligently and thoroughly in the framework of achieving production and as the highest variable the effect is the placement of employee positions that pay attention to the level of employee knowledge in accordance with the demands of the task.